A deeper insight into the sialome of male and female Ochlerotatus triseriatus mosquitoes. (August 2022) - Lu, Stephen; Martin-Martin, Ines; Ribeiro, Jose M.; Calvo, Eric
Abstract: Over the last 20 years, advancements in sequencing technologies have highlighted the unique composition of the salivary glands of blood-feeding arthropods. Further biochemical and structural data demonstrated that salivary proteins can disrupt host hemostasis, inflammation and immunity, which favors pathogen transmission. Previously, a Sanger-based sialome of adult Ochlerotatus triseriatus female salivary glands was published based on 731 expressed sequence tag (ESTs). Here, we revisited O. triseriatus salivary gland contents using an Illumina-based sequencing approach of both male and female tissues. In the current data set, we report 10, 317 DNA coding sequences classified into several functional classes. The translated transcripts also served as a reference database for proteomic analysis of O. triseriatus female saliva, in which unique peptides from 101 proteins were found. Finally, comparison of male and female libraries allowed for the identification of female-enriched transcripts that are potentially related to blood acquisition and virus transmission. Graphical abstract: Image 1 Highlights: Ochlerotatus triseriatus mosquitoes are the primary vector of La Crosse virus and other arbovirus. Salivary gland proteins help blood feeding and may enhance pathogen transmission. Transcriptomic and proteomic studies are instrumental in the understanding of biology of salivary components. A deeper insight into this sialome may lead to the discovery of novel pharmacologically active products.